2016
DOI: 10.1002/jqs.2905
|View full text |Cite
|
Sign up to set email alerts
|

Chronology and processes of late Quaternary hillslope sedimentation in the eastern South Island, New Zealand

Abstract: Optical and radiocarbon dating of loessic hillslope sediments in New Zealand's South Island is used to constrain the timing of prehistoric rockfalls and associated seismic events, quantify spatial and temporal patterns of landscape evolution, and examine hillslope responses to climatic and anthropogenic forcing. Exploratory trenches adjacent to prehistoric boulders enable stratigraphic analysis of loess and loesscolluvium pre-and post-boulder emplacement sediments. Luminescence ages from colluvial sediments co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 72 publications
1
13
0
Order By: Relevance
“…CES rockfalls were characterized by boulder-size distribution, runout distance (the distance a rock travels down a slope from its source), sourcearea dimensions, and boulder-production rates over a range of triggering peak ground accelerations (Massey et al, 2012a(Massey et al, -e, 2014(Massey et al, , 2017Quigley and Mackey, 2014;Quigley et al, 2016). Subsequent field investigations revealed an abundance of pre-CES rockfall deposits in CES rockfall areas (Townsend and Rosser, 2012;Mackey and Quigley, 2014;Borella et al, observations support the reported lithologic descriptions for the two study locales. The inferred strike and dip for lava flows nearest to the study sites indicates a shallow inclination in a predominantly northerly direction for measurements nearest the Rapaki and Purau study sites (Hampton and Cole, 2009).…”
Section: Introductionsupporting
confidence: 63%
“…CES rockfalls were characterized by boulder-size distribution, runout distance (the distance a rock travels down a slope from its source), sourcearea dimensions, and boulder-production rates over a range of triggering peak ground accelerations (Massey et al, 2012a(Massey et al, -e, 2014(Massey et al, , 2017Quigley and Mackey, 2014;Quigley et al, 2016). Subsequent field investigations revealed an abundance of pre-CES rockfall deposits in CES rockfall areas (Townsend and Rosser, 2012;Mackey and Quigley, 2014;Borella et al, observations support the reported lithologic descriptions for the two study locales. The inferred strike and dip for lava flows nearest to the study sites indicates a shallow inclination in a predominantly northerly direction for measurements nearest the Rapaki and Purau study sites (Hampton and Cole, 2009).…”
Section: Introductionsupporting
confidence: 63%
“…a) (Griffiths, ; Almond et al ., ), and cosmogenic 3 He dating of palaeorockfall boulders overlying the in situ loess (Mackey and Quigley, ). In situ loess at the Rapaki Study Site has been correlated to the Birdlings Flat loess (Borella et al ., , b). Intercalated volcanic ash within the Birdling's Flat loess (Fig.…”
Section: Site Description and Geological Contextmentioning
confidence: 97%
“…The palaeorockfall boulders identified on the same slope (Fig. b,c) have the same morphology, lithology and similar spatial distribution (except for maximum run‐out distance, see Borella et al, ) as modern boulders and imply that similar earthquakes are likely to have been responsible for past rockfall activity (Mackey and Quigley, ; Borella et al ., , b).…”
Section: Site Description and Geological Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Data availability. The research data can be publicly accessed at https://doi.org/10.5061/dryad.9km1t86(Borella et al, 2019).www.nat-hazards-earth-syst-sci.net/19/2249/2019/ Nat. Hazards Earth Syst.…”
mentioning
confidence: 99%